Evaluation of the Psychological Status of Infertile Women - Urfa Taj, Shazia Jabeen, Mahwish Pervaiz, Huma Fiaz, Faheema, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The birth of progeny is one of the most satisfying events. The infertility is one of the major concerns of the modern world. Although there are variable physical causes of infertility but the psychological stress is considered as one of the main causes of infertility. Objective: The fertility problem inventory was used to evaluate the psychological status of the infertile women. The relationship between psychological problems and characteristics of infertility was also assessed. Study design: It is a prospective and questionnaire-based study conducted for the duration of one year on the women attended the gynecology and obstetrician department of Allama Iqbal Memorial Teaching Hospital Sialkot. The study was conducted from June 2021 to May 2022. Material and Methods: A two-month prospective, quantitative, descriptive, questionnaire-based study was conducted on women undergoing infertility therapy with the approval of the institution's ethical committee. The stress level were analyzed by Fertility Problem Inventory Questionnaire. Excel and Microsoft was used for tabulation of data. The collected data was stratified by statistical analysis. The SPSS was used for the analysis. For the categorical variables the t-test was performed. Results: The average age of the twenty three patients included in the study was 30 years. The severe level of infertility-related stress was observed in the almost 75% of the included patients. The other 25% were suffering from the moderate level of stress. Conclusion: The serious psychological morbidity was observed in approximately two-third of the participants. Psychological evaluation of the patients taking infertility therapy could be a consideration. Keywords: Psychological problems and infertility therapy.